2022
DOI: 10.1103/physrevb.105.094521
|View full text |Cite
|
Sign up to set email alerts
|

Possible unconventional pairing in (Ca,Sr)3(Ir,Rh)4Sn13 superconductors revea

Abstract: We study the evolution of temperature-dependent resistivity with added pointlike disorder induced by 2.5 MeV electron irradiation in stoichiometric compositions of the "3-4-13" stannides, (Ca,Sr) 3 (Ir,Rh) 4 Sn 13 . Three of these cubic compounds exhibit a proposed microscopic coexistence of charge density wave (CDW) order and superconductivity (SC), while Ca 3 Rh 4 Sn 13 does not develop CDW order. As expected, the CDW transition temperature T CDW is universally suppressed by irradiation in all three composit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 125 publications
0
1
0
Order By: Relevance
“…Approximately below T < 0.35T c , all curves saturate, indicating exponential attenuation and, therefore, a fully gapped state at all x. Previously, we reported exponential attenuation in pure compounds x = 0 and x = 1, indicating a fully gaped Fermi surface [26]. However, probing the robustness of the superconducting state to disorder, we found a significant reduction of the transition temperature with non-magnetic scattering and it was concluded that 3-4-13 stannides are indeed fully gapped, but their order parameter is unconventional [26].…”
Section: London Penetration Depthmentioning
confidence: 72%
See 3 more Smart Citations
“…Approximately below T < 0.35T c , all curves saturate, indicating exponential attenuation and, therefore, a fully gapped state at all x. Previously, we reported exponential attenuation in pure compounds x = 0 and x = 1, indicating a fully gaped Fermi surface [26]. However, probing the robustness of the superconducting state to disorder, we found a significant reduction of the transition temperature with non-magnetic scattering and it was concluded that 3-4-13 stannides are indeed fully gapped, but their order parameter is unconventional [26].…”
Section: London Penetration Depthmentioning
confidence: 72%
“…The crystals were etched with HCl, cut with a wire saw, and polished to a typical size of (1 − 2) × 0.2 × 0.4 mm 3 . The contacts were formed by soldering 50 µm silver wires with tinsilver solder [25,26], with typical contact resistances below 100 µΩ.…”
Section: Electrical Resistivitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, the difference shown in Figure between Yb 3 Rh 4 Sn 13 and (Sn 1– x Tb x )­Tb 4 Rh 6 Sn 18 structure types resides in the prism arrangement, thus causing two distinct crystallographic sites for the A element. A detailed comparison between the Yb 3 Rh 4 Sn 13 and (Sn 1– x Tb x )­Tb 4 Rh 6 Sn 18 structure types is provided by Hodeau et al The (Sn 1– x Er x )­Er 4 Rh 6 Sn 18 structure type and its hettotype analogues have been of interest due to reports of tunability between reentrant superconductivity and magnetic ordering in (Sn 1– x Er x )­Er 4 M 6 Sn 18 (M = Rh and Os), , unconventional superconductivity in A 5 Rh 6 Sn 18 (A = Lu, Y, and Sc), noncollinear spin structure, and disorder-enhanced nonhomogeneous superconductivity in the Y 5−δ (Rh 5.5 M 0.5 )­Sn 18 compounds …”
Section: Remeika Phases: a Platform For Intermetallic Pseudoperovskitesmentioning
confidence: 99%